Հանրային քաղաքականությունը քաղաքացիական մշակույթի գործիք - Սարոյան Կնյազ (YSU Journal of International Affairs, 2017)
In the article it is highlighted the idea, that modern democratic regime types, especially electoral democracies with their representative institutes are facing serious problems in terms of legitimacy and public trust. From this point of view on the bases of analyses of Armenian domestic political processes, the article suggests considering the public policy as an effective tool of civic culture in the relations of public and policy makers. Consequently, the article argues, that deliberative democracy and discursive politics are believed to be robust instruments insuring deliberative civic engagement in the process of decision making in the Republic of Armenia.